1946-1951 Arası Bulgaristan’dan Türkiye’ye Müslüman Göçleri - Uzunca, Sevde (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
Bu tezde 1946-1951 yılları arasında Bulgaristan’dan Türkiye’ye gerçekleşmiş olan göçler incelenmiştir. Bahsi geçen yıllar hem Türkiye Cumhuriyeti hem de Bulgaristan için son derece önemli yıllardır. Öyle ki Türkiye için Çok Partili Döneme geçiş Bulgaristan için ise Krallığın kaldırılmasını ve Komünist yönetimi ifade etmektedir. Soğuk Savaş Döneminde bu iki devletin farklı bloklarda yer alması da aralarındaki siyaseti etkilemiştir. İki devletin farklı bloklarda yer alması birbirlerini tehdit olarak algılamalarına sebebiyet verirken bu durum en çok Bulgaristan’ın Müslüman ve Türk azınlığına yansımıştır. Müslüman azınlığın dinde fanatik ve köktenci görülmesinin yanı sıra Türkiye Cumhuriyeti’yle olan bağı da tehdit olarak algılanmıştır. Bu algılayış beraberinde asimilasyon, şiddet ve göçleri getirmiştir. Bu tezde bu algılayışın Türkiye’ye ve Müslüman azınlığa yansıması ele alınmıştır.

In this thesis; the migrations from Bulgaria to Turkey between 1946-1951 are have been studied The aforementioned years are extremely important for both the Republic of Turkey and Bulgaria. So much so that the transition to the Multi-Party Period for Turkey means exit from the empire and communist rule for Bulgaria. The fact that these two rulers were in different blocs during the Cold War period also affected the politics between them. This situation, which may cause the two states to be perceived as enemies occupying different blocs, was mostly reflected in the Muslim and Turkish minority in Bulgaria. In addition to the fanatical and fundamentalist appearance of the Muslim minority, its ties with the Republic of Turkey were perceived as a threat. With this perception, assimilation, violence and migration emerged. In this thesis, the general characteristics of this perception of Turkey and the Muslim minority are discussed.
Migration from Bulgaria to Turkey Between 1946-1951
Keywords: 1946-1951; Çok Partili Dönem; Komünizm; Bulgaristan; Soğuk Savaş; Pomak; Multi-Party Period; Communism; Bulgaria; Cold War; Pomaks